Manifestasi klinis dan derajat aktivitas penyakit pada penyandang Lupus Eritematosus Sitemik di Rumah Sakit Dr. Mohammad Hoesin Palembang - Partan, Radiyati Umi; Hermansyah, Hermansyah; Darma, Surya; Reagan, Muhammad; Muthia, Putri; Salim, Eddy Mart; Kriswiastiny, Rina; Kurniati, Nova; Yuniza, Yuniza; Silitonga, Aira Priamas (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that can affect various organs. Clinical manifestations vary from mild to severe depending on the organs involved. Manifestations of SLE in the kidney known as lupus nephritis can occur in 60% of the SLE population and are more common in Asian, Hispanic, Native American, and Black populations, especially in women of childbearing age, involvement of other organs such as neurology is referred to as neuropsychiatric lupus, as well as other organs can manifest such as mucocutaneous lupus, arthritis, pericarditis and other organs. This community service is carried out as a form of preventive treatment with counseling methods to increase knowledge and health checks for early detection of SLE, as well as promotive efforts for the SLE community in the disease polyclinic at Dr. Mohammad Hoesin Palembang, South Sumatra which is one of the teaching hospitals of the Faculty of Medicine, Sriwijaya University. This activity was attended by 35 people with SLE with several risk facts such as female gender and middle adulthood which is quite common, and some of the systemic clinical manifestations experienced are almost fatigue and fever, for musculoskeletal manifestations the most commonly experienced is arthritis, while the most common manifestations of other organs are mucocutaneous disorders. Keywords: Lupus, Autoimmune, Disease Activity